The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1970
DOI: 10.3329/bjar.v34i4.5840
|View full text |Cite
|
Sign up to set email alerts
|

<i>In vitro</i> micropropagation of banana

Abstract: The present study was conducted at the Biotechnology Laboratory, Biotechnology Division, Bangladesh Agricultural Research Institute (BARI), Gazipur during the period from September 2004 to June 2005 to investigate the effect of different concentrations of BAP and NAA on virus free plant regeneration, shoot multiplication and different concentrations of IBA and IAA on in vitro root formation of banana cv. BARI Banana-I. The culture meristem first turned brown in colour in 4-5 days which grew into a green globul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 4 publications
3
20
1
2
Order By: Relevance
“…These findings did not agree with the results of Al-Amin et al [25], where the MS media supplemented with BAP and NAA in their study showed different results for increasing shoot length Interactive effect of BAP and IAA was also observed in fresh weight (Figure 2). The media with 6 mg/l of BAP in combination with 0.35 mg/l IAA, significantly (p ≤ 0.01) resulted in high fresh weight as compared with other treatments ( Table 3).…”
Section: Open Access Ajpscontrasting
confidence: 88%
“…These findings did not agree with the results of Al-Amin et al [25], where the MS media supplemented with BAP and NAA in their study showed different results for increasing shoot length Interactive effect of BAP and IAA was also observed in fresh weight (Figure 2). The media with 6 mg/l of BAP in combination with 0.35 mg/l IAA, significantly (p ≤ 0.01) resulted in high fresh weight as compared with other treatments ( Table 3).…”
Section: Open Access Ajpscontrasting
confidence: 88%
“…The above mentioned results are in agreement with those of Gübbük and Pekmezci (2004), Gubbuk and Pekmezci (2006), Kalimuthu et al (2007), Shiragi et al (2008), Al-Amin et al (2009), Bhosale et al (2011), Mahadev et al (2011, Jafari et al (2013), Rahman et al (2013), Anbazhagan et al (2014), Mahdi et al (2014), Ngomuo and Ndakidemi (2014) and Shankar et al (2014). All of them found that BAP and kinetin increased the shoot number initiated from shoot tips of banana during micropropagation through tissue culture.…”
Section: Resultssupporting
confidence: 85%
“…Long generation time, various levels of ploidy, lack of genetic variability, and sterility of most edible cultivars have hampered the development of disease-resistant Musa by conventional breeding (Stover and Buddenhagen 1986;Stover and Simmonds 1987;Swennen and Vuylsteke 1993;Musoke et al 1999;Pillay et al 2004;Tripathi et al 2004). In vitro micropropagation has played a key role in clonal propagation of banana for obtaining large numbers of homogenous plants and breeding of plantains and bananas (Pierik 1987;Rowe and Rosales 1996;Vuylsteke et al 1997;Kalimuthu et al 2007;Al-Amin et al 2009). …”
Section: Introductionmentioning
confidence: 99%